The contribution of cerebellar proton magnetic resonance spectroscopy in the differential diagnosis among parkinsonian syndromes. Issue 8 (August 2015) - Zanigni, Stefano; Testa, Claudia; Calandra-Buonaura, Giovanna; Sambati, Luisa; Guarino, Maria; Gabellini, Anna; Evangelisti, Stefania; Cortelli, Pietro; Lodi, Raffaele; Tonon, Caterina
Abstract Introduction The in vivo differential diagnosis between idiopathic Parkinson's disease (PD) and atypical parkinsonian syndromes (PS), such as multiple system atrophy [MSA with a cerebellar (C) and parkinsonian (P) subtype] and progressive supranuclear palsy – Richardson's Syndrome (PSP-RS) is often challenging. Previous brain MR proton spectroscopy (1H-MRS) studies showed biochemical alterations in PS, despite results are conflicting. Cerebellum plays a central role in motor control and its alterations has been already demonstrated in atypical PS. The main aim of this study was to evaluate diagnostic accuracy of cerebellar 1H-MRS in the differential diagnosis between PD and atypical PS. Methods We obtained 1H-MRS spectra from the left cerebellar hemisphere of 57 PS (21 PD, and 36 atypical PS) and 14 unaffected controls by using a 1.5 T GE scanner. N-acetyl-aspartate (NAA)/Creatine (Cr), choline-containing compounds (Cho)/Cr, myoinositol (mI)/Cr, and NAA/mI ratios were calculated. Results NAA/Cr and NAA/mI ratios were significantly lower (p < 0.01) in atypical PS compared to PD and controls, and in MSA-C compared to PD, MSA-P, PSP-RS and controls. PSP-RS group showed reduced NAA/Cr ratios compared to PD (p < 0.05) and controls (p < 0.05), and reduced NAA/mI compared to controls (p < 0.01). NAA/Cr ratio values higher than 1.016 showed 100% sensitivity and negative predictive value, 62% positive predictive value and 64% specificity in discriminating PD. Conclusion Cerebellar biochemical alterations detected by using 1H-MRS could represent an adjunctive diagnostic tool to improve the differential diagnosis of PS.